Die toksikologiese telefoniese konsultasies gerig aan die Departement Farmakologie van die Universiteit van die Vrystaat gedurende 1998 - C.J. Engelbrecht; J. Folmer; W.C. Steyn; G. Joubert; N. Fourie (South African Family Practice)
Background: Epidemiologic surveys of poisonings as well as inquiries regarding poisonings are necessary to obtain information for the combating as well successful medical management of poisonings.